2016
DOI: 10.1016/j.semcdb.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Inactive rhomboid proteins: New mechanisms with implications in health and disease

Abstract: Rhomboids, proteases containing an unusual membrane-integral serine protease active site, were first identified in Drosophila, where they fulfill an essential role in epidermal growth factor receptor signaling, by cleaving membrane-tethered growth factor precursors. It has recently become apparent that eukaryotic genomes harbor conserved catalytically inactive rhomboid protease homologs, including derlins and iRhoms. Here we highlight how loss of proteolytic activity was followed in evolution by impressive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 98 publications
1
38
0
Order By: Relevance
“…We reported that iRhoms control transport of TACE from the ER to the Golgi apparatus, where removal of its pro-domain by pro-protein convertases such as furin occurs (Endres et al, 2003). In this way, iRhoms regulate the conversion of TACE from an inactive immature form to a mature proteolytically competent shedding enzyme (Adrain and Freeman, 2012; Freeman, 2014; Lemberg and Adrain, 2016). Without iRhoms there is no TACE maturation and therefore no TACE activity (Christova et al, 2013; Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that iRhoms control transport of TACE from the ER to the Golgi apparatus, where removal of its pro-domain by pro-protein convertases such as furin occurs (Endres et al, 2003). In this way, iRhoms regulate the conversion of TACE from an inactive immature form to a mature proteolytically competent shedding enzyme (Adrain and Freeman, 2012; Freeman, 2014; Lemberg and Adrain, 2016). Without iRhoms there is no TACE maturation and therefore no TACE activity (Christova et al, 2013; Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…iRhoms comprise a seven transmembrane rhomboid-like domain, with a short luminal C-terminus, a well conserved loop between TMDs 1 and 2 (termed the iRhom homology domain, IRHD), and a long cytoplasmic N-terminus (Lemberg and Freeman, 2007, 2016). There is accumulating physiological and cell biological evidence that mutation or deletion of the cytoplasmic N-terminus of iRhoms leads to alterations in TACE function (Johnson et al, 2003; Blaydon et al, 2012; Saarinen et al, 2012; Brooke et al, 2014; Hosur et al, 2014; Siggs et al, 2014; Liu et al, 2015; Maney et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is independent of its rhomboid intramembrane protease activity, but requires the enzyme active site, and resembles the function of eukaryotic rhomboid pseudoproteases. The latter are membrane proteins that exhibit the rhomboid fold, but have lost their catalytic activity during evolution, while retaining or developing new functions such as the specific recognition or dislocation of proteins from the membrane (Lemberg & Adrain, ). Likewise, derlins act as rhomboid pseudoproteases in eukaryotic ERAD of both soluble and integral membrane proteins (Greenblatt et al , ; Neal et al , ).…”
Section: Rhomboid Proteases and Pseudoproteases Target Proteins For Dmentioning
confidence: 99%
“…Rhomboids were identified as intramembrane proteases that cleave growth factors to control intercellular signalling in Drosophila, but over the past 5 years, rhomboid-like proteins have emerged as serving a wide variety of important catalytic and non-catalytic functions (Lemberg and Adrain, 2016). Matthew Freeman (University of Oxford, UK) reported an important physiological role for a rhomboid-like protein in the control of lipid homeostasis in mammals.…”
Section: Ubiquitin and The Proteasomementioning
confidence: 99%
“…Matthew Freeman (University of Oxford, UK) reported an important physiological role for a rhomboid-like protein in the control of lipid homeostasis in mammals. Ioanna Oikonomidi (IGC, Oeiras, Portugal) focused on a novel regulator of the iRhom-ADAM17 axis, a pathway important for inflammatory and growth factor signalling (Lemberg and Adrain, 2016). Kvido Strisovsky (Institute of Organic Chemistry and Biochemistry, Prague, Czech Republic) reported a novel physiological role for a bacterial rhomboid protease in protein quality control which impacted on ion homeostasis in vivo.…”
Section: Ubiquitin and The Proteasomementioning
confidence: 99%